2020
DOI: 10.1038/s41389-020-00251-5
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing DRP1-mediated mitochondrial fission and mitophagy increases mitochondrial apoptosis of hepatocellular carcinoma cells in the setting of hypoxia

Abstract: Transarterial embolization/transarterial chemoembolization (TAE/TACE) is the acceptable palliative treatment for hepatocellular carcinoma (HCC), mainly through ischemic necrosis induced by arterial embolization. However, how HCC cells survive under such ischemic hypoxic condition remains unclear, which can be exploited to potentiate TAE/ TACE treatment. We hypothesized that targeting mitophagy can increase HCC cell apoptosis during hypoxia. HCC cells were subjected to hypoxia and then mitophagy was quantified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 55 publications
(66 reference statements)
3
31
1
Order By: Relevance
“…Specifically, the open reading frame ORF9b protein of SARS-CoV bind the outer mitochondrial membrane in A549, HEK 293, and THP-1 cellular models and facilitate the degradation of Dynamin-related protein (Drp1) through ubiquitination that ultimately causes mitochondrial elongation [60]. Drp1 is a GTPase required for mitochondrial fission, an essential process by which dysfunctional mitochondria are eliminated through mitophagy [82][83][84][85][86]. However, the exact consequence of this mitochondrial elongation is unclear, but it is believed to alter mitochondrial dynamics, favoring viral replication.…”
Section: Open Reading Frame 9b (Orf9b)mentioning
confidence: 99%
“…Specifically, the open reading frame ORF9b protein of SARS-CoV bind the outer mitochondrial membrane in A549, HEK 293, and THP-1 cellular models and facilitate the degradation of Dynamin-related protein (Drp1) through ubiquitination that ultimately causes mitochondrial elongation [60]. Drp1 is a GTPase required for mitochondrial fission, an essential process by which dysfunctional mitochondria are eliminated through mitophagy [82][83][84][85][86]. However, the exact consequence of this mitochondrial elongation is unclear, but it is believed to alter mitochondrial dynamics, favoring viral replication.…”
Section: Open Reading Frame 9b (Orf9b)mentioning
confidence: 99%
“…The proliferation and invasion of tumor cells also require faster and increased energy supply ( 79 ). Thus, Drp1 expression is upregulated in several types of cancer cells, including liver ( 80 ), breast ( 81 ) and lung cancers ( 82 ), and may be considered as a biomarker for predicting poor survival in patients with these types of cancer. A study on ovarian cancer demonstrated that glycolysis is promoted by activating PI3K/AKT/HIF-1α signaling, while mitochondrial fission is enhanced by phosphorylation of Drp1 at Ser616 ( 83 ).…”
Section: Association Between Mitochondrial Dynamics and Energy Metabomentioning
confidence: 99%
“…Combined with our findings, we speculated that lung injury caused by hyperoxia in newborn rats would increase mitochondrial fission, namely the expression of Drp1, due to oxidative stress. In addition, experiments have confirmed the relationship between hypoxia and Drp1, studies were not only involved in animal models about Lung Ischemia-reperfusion Injury (30) and lung vascular ischemic/hypoxic injury (31), but also in others like hepatocellular carcinoma cells in hypoxia (32), and Hypoxia-Reoxygenation Injury of Cardiomyocytes (33). Although hypoxia or hyperoxia can trigger similar pathological responses, such as oxidative stress and inflammation, these underlying mechanisms need to be further studied at the cellular level.…”
Section: Discussionmentioning
confidence: 99%